Uptake of hepatitis C virus treatment in HIV/hepatitis C virus-coinfected patients across Europe in the era of direct-acting antivirals. (10th September 2018) - Peters, Lars; Laut, Kamilla; Resnati, Chiara; Del Campo, Santos; Leen, Clifford; Falconer, Karolin; Trofimova, Tatyana; Paduta, Dzmitry; Gatell, Jose; Rauch, Andri; Lacombe, Karine; Domingo, Pere; et al.
Abstract : Background and aims: To investigate the uptake of hepatitis C virus (HCV) therapy among HIV/HCV-coinfected patients in the pan-European EuroSIDA study between 2011 and 2016. Methods: All HCV-RNA+ patients were included. Baseline was defined as latest of anti-HCV+, January 2011 or enrolment in EuroSIDA. The incidence of starting first interferon-free direct-acting antiviral (DAA) therapy was calculated. Factors associated with starting interferon-free DAA were determined by Poisson regression. Results: Among 4308 HCV-RNA+ patients (1255, 970, 663, 633, 787 from South, West, North, Central East and East Europe, respectively) with 11 863 person-years of follow-up, 1113 (25.8%) started any HCV therapy. Among patients with at least F3 fibrosis, more than 50% in all regions remained untreated. The incidence (per 1000 person-years of follow-up, 95% confidence interval) of starting DAA increased from 7.8 (5.9–9.8) in 2014 to 135.2 (122.0–148.5) in 2015 and 128.9 (113.5–144.3) in 2016. The increase was highest in North and West and intermediate in South, but remained modest in Central East and Eastern Europe. After adjustment, women, individuals from Central East or East, genotype 3, antiretroviral therapy naïve and those with detectable HIV-RNA were less likely to start DAA. Older persons, those with HCV-RNA more than 500 000 IU/ml and those with more advanced liver fibrosis were more likely to start DAA. Conclusion: Uptake of DAA therapy among HIV/HCV-coinfected patients increased considerably in Western Europe between 2014 and 2016, but was modest in Central East and East. In all regions more than 50% with at least F3 fibrosis remained untreated. Women were less likely to start DAA.